الحوكمة المصرفية كآلية لتعزيز المسؤولية الاجتماعية بالبنوك والمؤسسات المالية في الجزائر -دراسة ميدانية بمجموعة من البنوك والمؤسسات المالية بولاية سطيف- - مزيمش, مزيمش أسماء; شريقي, شريقي عمر (Recherches économiques et managériales, 2020)
يهدف هذا البحث لدراسة الدور الذي تؤديه الحوكمة المصرفية في تعزيز المسؤولية الاجتماعية في البنوك والمؤسسات المالية وما هي العلاقة بينهما، وذلك من خلال التطرق للمفاهيم الخاصة بالحوكمة المصرفية والمفاهيم الخاصة بالمسؤولية الاجتماعية، ومن ثم دراسة الحوكمة المصرفية كآلية لتعزيز المسؤولية الاجتماعية في البنوك والمؤسسات المالية، من خلال دراسة ميدانية على مجموعة من البنوك والمؤسسات المالية في ولاية سطيف. وقد بيّنت نتائج الدراسة أن البنوك والمؤسسات المالية بولاية سطيف تطبق مبادئ الحوكمة المصرفية وهو أساس التزامها بالمسؤولية الاجتماعية، كما أن آليات الحوكمة المتمثلة في مجلس الإدارة، لجنة التدقيق، التدقيق الداخلي، التدقيق الخارجي واللجنة المصرفية، تعمل على تعزيز المسؤولية الاجتماعية بالبنوك والمؤسسات المالية محل الدراسة. الكلمات المفتاحية: الحوكمة، الحوكمة المصرفية، المسؤولية الاجتماعية، البنوك، المؤسسات المالية. Abstract: This research aims to examine the role played by the banking governance in promoting social responsibility in banks and financial institutions, and the relationship between them, through addressing the concepts of banking governance and social responsibility concepts, and then examine the Banking governance as a mechanism to promote social responsibility in banks and financial institutions, through field study on a group of banks and financial institutions in Setif.  The results of the study showed that banks and financial institutions in Setif are applying banking governance principles which are the basis of its commitment to social responsibility. Governance mechanisms, namely the administration Board, Audit Committee, internal audit, external and Banking Commission are working to promote social responsibility by banks and financial institutions that are the subject of the study.  Keywords: governance, banking governance, social responsibility, banks, financial institutions.